Pyrolysis 2017
DOI: 10.5772/67706
|View full text |Cite
|
Sign up to set email alerts
|

Pyrolysis of Polyolefins in a Conical Spouted Bed Reactor: A Way to Obtain Valuable Products

Abstract: The amount of waste plastic increases every single year, which causes a critical environmental issue. Polyolefins (mainly high-and low-density polyethylene and polypropylene) are the most common types of plastics, accounting for 60 wt% of the plastic waste. Pyrolysis, the thermal degradation in an inert atmosphere, is considered to be one of the most appealing technologies for the recycling of plastic materials. The conical spouted bed reactor is suitable for the pyrolysis of plastic waste due to its ability t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 33 publications
0
11
0
2
Order By: Relevance
“…Cyclic and vigorous movements by sand particles in the bed prevent agglomeration upon melting and subsequent bed defluidization. 275,337 Conical spouted beds have been employed in laboratory-scale pyrolysis studies of PS 338 and polyolefins, 337,[339][340] which report high yields of wax. Orozco et al 275 identified stable operating conditions for conical spouted bed reactors for individual plastic feedstocks.…”
Section: Reactor Configurationsmentioning
confidence: 99%
“…Cyclic and vigorous movements by sand particles in the bed prevent agglomeration upon melting and subsequent bed defluidization. 275,337 Conical spouted beds have been employed in laboratory-scale pyrolysis studies of PS 338 and polyolefins, 337,[339][340] which report high yields of wax. Orozco et al 275 identified stable operating conditions for conical spouted bed reactors for individual plastic feedstocks.…”
Section: Reactor Configurationsmentioning
confidence: 99%
“…Cyclic and vigorous movements by sand particles in the bed prevent agglomeration upon melting and subsequent bed defluidization. 259,326 Conical spouted beds have been employed in laboratory-scale pyrolysis studies of PS 327 and polyolefins, 326,[328][329] which report high yields of wax. Orozco et al 259 identified stable operating conditions for conical spouted bed reactors for individual plastic feedstocks.…”
Section: Reactor Configurationsmentioning
confidence: 99%
“…Also, the design of CSBR prevents agglomeration of sticky solids at the surface unlike a conventional fluidized bed reactor, thus allowing simpler operations. 205 Soharabi and co-workers 206 studied the kinetics of PET pyrolysis in a spouted bed reactor, wherein the activation energies of feed particles of sizes 0.1−1.0 and 1.0−3.0 mm were determined as 276.8 and 264.3 kJ/mol, respectively. The study concluded that heat and mass transfer limitations in spouted bed reactors could be minimized.…”
Section: Polypropylene (Pp)mentioning
confidence: 99%
“…The advantages of high heat and mass transfer, low residence time, and improved product quality remain the same as a fluidized bed reactor. Also, the design of CSBR prevents agglomeration of sticky solids at the surface unlike a conventional fluidized bed reactor, thus allowing simpler operations …”
Section: Pyrolysis Of Plastic Wastementioning
confidence: 99%